Production of Mite-Pathogenic Akanthomyces attenuatus JEF-147 Blastospores in Flask and Bioreactor Conditions - Gahyeon Song; Mi Rong Lee; Jae Su Kim (Mycobiology)
Mite-pathogenic Akanthomyces attenuatus JEF-147 was liquid-cultured to produce blastospores as an active ingredient of formulations, which is more practical and cost-effective method than currently used solid cultures although stress resistance remains a challenge. In this work, first starch- or glucose-based artificial liquid culture media were used to culture JEF-147 with high miticidal activity against two-spotted spider mites (Tetranychus urticae) in flask conditions. The starch-based medium produced significantly higher numbers of blastospores than the glucose-based medium. JEF-147 blastospores from the glucose-based medium showed faster pathogenesis than those from starch-based medium. This liquid cultured was scaled up in a 2.5-L bioreactor with the glucose-based medium and 1.0 v/v/m of air supply. Production of blastospores was initiated 36 h after inoculation, but active blastospore production was not observed even in 94 h. Alternatively, the glucose-based medium was supplemented with magnesium sulfate at 1% (w/w) in the same bioreactor conditions, and it produced large number of blastospores. This work suggests that JEF-147 blastospores from the glucose-based liquid culture could be used for mite control and the supplement of salt to the medium possibly ensures the production of blastospores in a scale-up conditions. Specific optimization of salt and culture parameters in the scale up conditions and field study would be essential works to be followed.